Sustained Response to Entrectinib in an Infant With a Germline ALKAL2 Variant and Refractory Metastatic Neuroblastoma With Chromosomal 2p Gain and Anaplastic Lymphoma Kinase and Tropomyosin Receptor Kinase Activation. (27th January 2022) - Treis, Diana; Umapathy, Ganesh; Fransson, Susanne; Guan, Jikui; Mendoza-García, Patricia; Siaw, Joachim T.; Wessman, Sandra; Gordon Murkes, Lena; Stenman, Jakob J. E.; Djos, Anna; Elfman, Lotta H. M.; Johnsen, John Inge; et al.
Abstract :